Analysis of Production Costs on The Income of Broiler Chicken Farming Businesses - Ibnu Pribadi Salim; Hamdi Mayulu; Ardiansyah; Dede Aprylasari (FEB Universitas Mulawarman, 2026)
Broiler farming is crucial for providing animal protein and enhancing the income of farm households; however, rising production costs often impede business efficiency. This study examined how various production cost factors affect broiler farm income in a commercial closed-house production system. A quantitative case study approach was used, drawing on primary and secondary data collected over one production cycle. The study's independent variables included expenses for chicks, feed, labor, medication and vaccines, electricity and water, and housing depreciation, whereas farm income served as the dependent variable. Multiple linear regression analysis was performed to evaluate the collective and individual effects. The results showed that feed costs accounted for the largest share of total production expenses, representing 61.3%. The total revenue was IDR 229,405,000, and the production costs totaled IDR 110,500,000, leading to a farm income of IDR 118,905,000 per cycle. A correlation coefficient of 0.927 indicates a very strong relationship between production costs and income, and a determination coefficient of 0.859 suggests that 85.9% of the income variation is explained by the model. Partial regression analysis confirmed that all production cost components significantly affected income, with feed costs having the most pronounced negative effect. Therefore, effectively managing feed and other operational costs is essential for improving the profitability and sustaining the performance of broiler farms.